The Root of the Finitude of Ens: Self-Determination and Potentiality of Esse According To Étienne Gilson: Autodeterminación y potencialidad del esse según Étienne Gilson - Giordano, Cecilia (Scripta Mediaevalia, 2025)
This paper aims to raise the issue of the finitude of ens based on its constitutive principles, in Gilson’s interpretation of Thomas Aquinas. Being the essence, limiting principle and receiving subject of esse, the entitative finitude seems to fall upon it. However, we explore the hypothesis that it is the very esse – relatively to the essence – the principle of such finitude. This seems to be indicated by Gilson when speaking of self-determination of esse, a degree of intensity, reciprocity, and quantity or measure of being, all of which would imply a potential aspect of the act of being. This would question the relationship between act and potency, as well as the relationship between recipient-received, held by Aquinas. In this regard, we understand that Gilson’s development of the notion of virtus essendi is key to redefining the previous hypothesis, and responding to the issue raised.